2023
DOI: 10.1093/g3journal/jkad154
|View full text |Cite
|
Sign up to set email alerts
|

GWLD: an R package for genome-wide linkage disequilibrium analysis

Abstract: Linkage disequilibrium (LD) analysis is fundamental to the investigation on genetic architecture of complex traits (e.g. human disease, animal and plant breeding), and population structure and evolution dynamics. However, until now, studies primarily focus on LD status between genetic variants located on the same chromosome. Moreover, genome (re-)sequencing produces unprecedented numbers of genetic variants, and fast LD computation becomes a challenge. Here, we have developed GWLD, a parallelized and generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Therefore, LD analysis is a fundamental step in association analysis. The degree of LD between loci can be reflected in the D value and r 2 [51,52]. Qi et al [20] used SSR markers to analyze the linkage disequilibrium of barley populations and found that the range of D values was mainly concentrated between 0 and 0.6, accounting for 82.06% of the paired 992 SSR marker sites.…”
Section: Linkage Disequilibrium Analysis Of P Juncea Populationmentioning
confidence: 99%
“…Therefore, LD analysis is a fundamental step in association analysis. The degree of LD between loci can be reflected in the D value and r 2 [51,52]. Qi et al [20] used SSR markers to analyze the linkage disequilibrium of barley populations and found that the range of D values was mainly concentrated between 0 and 0.6, accounting for 82.06% of the paired 992 SSR marker sites.…”
Section: Linkage Disequilibrium Analysis Of P Juncea Populationmentioning
confidence: 99%